Report of the Working Group on Agricultural Production for the Formulation of Seventh Five Year Plan Part I Analytical and Conceptual - Planning Commission (Planning Commission, 1983)
A Working Group on Agricultural Production for the Seventh Five Year Plan was set up by the Planning Commission (vide Planning Commission's O.M. No. M-12043/3/83-Agri. dated 26th October, 1983) with the undersigned as the Chairman and Joint Secretary (Extension) in this Ministry as the Member- Secretary. The Working Group, after holding three sittings, prepared a draft which was placed before the Committee on Directions on 27th August, 1984. The Report was revised in the light of the observations made by the Committee and the Group met for the fourth time to finalise it. The final draft was considered by the Committee on Directions on 20th September, 1984, when it was approved.
Part I Analytical and Conceptual
Government of India Planning Commission
Keywords: Past performance and financial outlays for Agriculture Sector in the earlier Plans; Review of past performance; Financial outlays for Agriculture Sector in the earlier Plans; Analysis of past performance of Indian agriculture; Spread of modern technology; Performance in respect of some parameters; Measures to increase the effectiveness of research-extension set-up; Targets of foodgrain production for the Seventh Plan; Key issues for the Seventh Five Year Plan